2018
DOI: 10.1088/1361-6587/aab175
|View full text |Cite
|
Sign up to set email alerts
|

The formation and dissipation of electrostatic shock waves: the role of ion–ion acoustic instabilities

Abstract: The role of ion-ion acoustic instabilities in the formation and dissipation of collisionless electrostatic shock waves driven by counter-streaming supersonic plasma flows has been investigated via two-dimensional particle-in-cell simulations. The nonlinear evolution of unstable waves and ion velocity distributions has been analyzed in detail. It is found that for electrostatic shocks driven by moderate-velocity flows, longitudinal and oblique ion-ion acoustic instabilities can be excited in the downstream and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Our simulations show that this relative drift is driven by the E TNSA in the upstream plasma which results in slower moving heavier ions with low hZ=Ai and faster moving protons with high hZ=Ai. Simulations done by Zhang [26] have shown that in the transverse size-reduced simulation EITI propagates in the x-direction, whereas in the large transverse size simulation it propagates obliquely. In our case, since the propagation directions of EITI are in the x-direction both for the small and the large transversesize simulations [Figs.…”
Section: A Collisionless Shock Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our simulations show that this relative drift is driven by the E TNSA in the upstream plasma which results in slower moving heavier ions with low hZ=Ai and faster moving protons with high hZ=Ai. Simulations done by Zhang [26] have shown that in the transverse size-reduced simulation EITI propagates in the x-direction, whereas in the large transverse size simulation it propagates obliquely. In our case, since the propagation directions of EITI are in the x-direction both for the small and the large transversesize simulations [Figs.…”
Section: A Collisionless Shock Formationmentioning
confidence: 99%
“…This leads to the excitation of an electrostatic ion two-stream instability (EITI) [23], which in turn enhances the number of the shockaccelerated protons [24]. To our best knowledge, most of the previous work has focused on shock formation [25][26][27] and ion heating [28][29][30]. This paper is the first investigation on the material (or hZ=Ai) dependence of EITI on CSA.…”
Section: Introductionmentioning
confidence: 99%
“…Counter-beaming plasma systems are of particular interest in astrophysical and experimental setups [18][19][20][21], i.e., in fusion and plasma experiments the interest is to avoid the formation of escaping beams and stabilize plasma systems, while in astrophysics plasma beams are widely invoked, likely, at the origin of various emissions and fluctuations which trigger their relaxation [22][23][24]. Energetic beams with speed exceeding the mean thermal speed are highly susceptible to electrostatic instabilities [25], and the electromagnetic modes may only hardly compete in nonrelativistic conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, this shielding is not perfect because of electron thermal motions, resulting potentials of the order of kT e /e ∼ kV can leak out [23], as shown in figure 3 (the three curves in blue, red, and black). On the other hand, the formation of the fine-structure electric field behind the shock front is due to the ion-ion acoustic instability [24]. The upstream ions have been decelerated to subsonic velocities after being transmitted into the downstream region in this process.…”
Section: Electrostatic Shock Generation Due To the MIX Of Au-he Plasmamentioning
confidence: 99%